Cracking Open Bacterial Membrane Vesicles - Nagakubo, Toshiki; Nomura, Nobuhiko; Toyofuku, Masanori (Frontiers in Microbiology, 2020)
Membrane vesicles (MVs) are nanoparticles composed of lipid membranes that are produced by both Gram-negative and Gram-positive bacteria. MVs have been assigned diverse biological functions, and they show great potential for applications in various fields. However, the mechanisms underlying their functions and biogenesis are not completely understood. Accumulating evidence shows that MVs are heterogenous, and different types of MVs with different compositions are released from the same species. To understand the origin and function of these MVs, determining the biochemical properties of MVs is important. In this review, we will discuss recent progress in understanding the biochemical composition and properties of MVs.